Actual condition of technical assistance and incidence on agriculture performance in Bolívar, Colombia - Maza -Avila, Francisco Javier; Fuentes -Maturana, Jeraldin; Franco -Santamaría, Jessica Paola (Universidad Francisco de Paula Santander, 2019)
AbstractThe objective of this article is to characterize the current state of technical assistance among agricultural producers in the department of Bolivar, as well as its impact on the final yield of their crops. For this purpose, the statistics of the III National Agricultural Census have been used, as well as the database of the Agricultural Information System -AGRONET-of the Ministry of Agriculture and Rural Development. The results show that few agricultural producers in the department of Bolívar receive technical assistance service, responding to the trend at the national level. On the other hand, no significant differences in agricultural performance were found between agricultural producers who receive the technical assistance service compared to those who do not.